Analysis of the Causes of Thread Cone Products Below the Tensile Strength Index Value - Parmawati, Sih; Nugraheni, Dyah Novia (Global Writing Academica Researching & Publishing, 2024)
Yarn spinning is an important aspect of the world of textiles. This is because spinning is the main focus of the textile industry sub-sector. Therefore, when yarn products are not suitable, this can have an impact on consumers and companies. This research then aims to look at the problem of the non-standard strength index of 30 TR 65/35 process cone threads using a problem-solving method through the PDCA concept. This research will be carried out using semi-quantitative methods. The analysis method used incorporates concepts from FTA (Fault Tree Analysis) and PDCA. The results of this research then found that the case study at PT X identified the main cause of non-standard tensile strength of 30 TR yarn as a combination of material suitability, machine condition, and environmental factors which had the most significant impact. The use of SFX brand polyester fiber and SPV brand rayon as raw materials, as well as an appropriate waste reuse sorting process, has been proven to increase the quality of the tensile strength of the yarn. Errors in twist values and suboptimal machine maintenance were also found to contribute to a decrease in yarn tensile strength. Production environmental conditions, such as high humidity, have a negative effect on yarn strength. An effective solution to this problem was found by adding wax to the thread, increasing its tensile strength by 7%.